MOBILITY AND RESISTANCE IN YOUNG INDIGENOUS AUSTRALIAN WRITING; READING TRAVEL NARRATIVES IN TARA JUNE WINCH’S SWALLOW THE AIR (Universitas Pamulang, 2020)
Considered as writing back to the Empire, postcolonial writing by young indigenous Australian offers different insight and perspective of their identity. One of postcolonial tendencies is re-define their own experience of space and place in contemporary Australia. Mobility and travel become method on experiencing the ancestor’s land. Many of Australian indigenous writing is about mobility, both physical and non-physical. This paper aims to elaborate mobility and mode of resistance in Tara June Winch’ Swallow the Air as young Australian Indigenous writing.Swallow the Air portrays journey of a young half-Indigenous descent across Australia. The journey is an attempt to translate past stories of Indigenous knowledge to the modern-day Australia. Instead of encountering the authentic, she finds out the long-lost landscape, tradition, mythology, and community. The travel narrative depicted in this novel is the contestation between the subjective expectation and objective reality. Lingering between fact and fiction, travel writing is a negotiation between the objective reality and subjective representation. By focusing on writer’s representation on the travel narrative, this paper aims to elaborate how mobility becomes mode of resistance.This research shows that othering occurs not only to the strange geography, people, and culture, but also inner strangeness to the self; a half European-Wiradjuri descent. Her encounters and dialogs to various landscapes and communities searching for home narrates metaphor of survival. The travel narrative accommodates the mobility, which offers a resistance toward fixation of identity—binary opposition between Indigenous and West. Other than spatial othering, Swallow the Air shows the tendency of temporal differentiation, comparing the past utopian fantasy with modern-day Australia. Melancholia occurs as the central theme of the journey as the failure to fulfill the utopian expectation—the loss of authentic Indigenous land, people, and culture. The mode of resistance offered in this melancholic travel narrative is the effort of preserving what is left—from the authentic utopian fantasy—Indigenous knowledge, inheritance, and memories, both personal and communal.Keywords: Mobility, Travel Writing, Indigenous, Australia, Postcolonial